The Javanese philosophy behind the panakawan characters: An Ethnolinguistic analysis of the play Semar Mbangun Kahyangan - Afendy Widayat; Ghis Nggar Dwiadmojo (Indonesian Journal of Applied Linguistics, 2023)
This ethnolinguistic analysis delves into the world of Panakawan characters in the Javanese play "Semar Mbangun Kahyangan," unveiling the profound tapestry of Javanese philosophy into their portrayal. The Panakawan, celebrated for their wit and linguistic artistry, stand as iconic figures in traditional Javanese wayang (shadow puppetry) and theater. This study explored their linguistic and cultural dimensions, illuminating their role as carriers of Javanese wisdom and cultural values. Employing ethnolinguistic methods, it examined the linguistic features, discourse patterns, and cultural intricacies interwoven within the dialogues and actions of the Panakawan characters. The analysis uncovers language's role in conveying Javanese philosophical concepts, moral teachings, and the interconnectedness of life and society within the play. It dissected the linguistic strategies, humor, and linguistic playfulness of the Panakawan, revealing their capacity to impart profound philosophical messages while captivating audiences. Furthermore, this study also revealed the inseparable bond between language, culture, and the embodiment of Javanese philosophy in the play "Semar Mbangun Kahyangan." It offers insights into the Panakawan's function as cultural emissaries and guardians of the Javanese ethos. This ethnolinguistic exploration extends an invitation to readers to uncover the concealed Javanese philosophy within the eloquent expressions and deeds of the Panakawan. It is expected to provide a significant contribution to ethnolinguistics, cultural studies, and philosophy by spotlighting the Panakawan characters' pivotal role as conduits for conveying the profound philosophy that shapes Javanese culture and character.